RNA editing of microRNA prevents RNA-induced silencing complex recognition of target mRNA. Issue 12 (December 2015) - Cui, Yalei; Huang, Tianzhi; Zhang, Xiaobo
Abstract : MicroRNAs (miRNAs) integrate with Argonaut (Ago) to create the RNA-induced silencing complex, and regulate gene expression by silencing target mRNAs. RNA editing of miRNA may affect miRNA processing, assembly of the Ago complex and target mRNA binding. However, the function of edited miRNA, assembled within the Ago complex, has not been extensively investigated. In this study, sequence analysis of the Ago complex of Marsupenaeus japonicus shrimp infected with white spot syndrome virus (WSSV) revealed that host ADAR (adenosine deaminase acting on RNA) catalysed A-to-I RNA editing of a viral miRNA (WSSV-miR-N12) at the +16 site. This editing of the non-seed sequence did not affect association of the edited miRNA with the Ago protein, but inhibited interaction between the miRNA and its target gene ( wsv399 ). The WSSV early gene wsv399 inhibited WSSV infection. As a result, the RNA editing of miRNA caused virus latency. Our results highlight a novel example of miRNA editing in the miRNA-induced silencing complex.